ECO-HARMONY AND ECONOMIC EQUITY: A VINDICATION OF GANDHIAN ECONOMICS - Pushparajan, A (Journal of Dharma, 1993)
It is an obvious fact that the world economy has become dangerously lopsided. The North, including the Eastern Europe, constitutes just one fourth of the world's population. And yet it consumes 80 percent of the world's resources. In sharp contrast to it, the South, including China, accounts for the three fourths of the world's population. But it has to content itself with the remaining 20 percent of the world's resources.